Breathable and moisture-permeable filling material

By uniformly mixing fine denier polyester fiber, acetate fiber, porous hollow polyester fiber and low melting point fiber, the filling material is solved, and the problem of not being breathable and not being able to quickly release moisture after being dampened in summer is solved, and high breathability, quick drying and comfortable feel is achieved, improving sleep and life quality.

CN119553425APending Publication Date: 2025-03-04SHANGHAI SHENGKUAI TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410998124.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The fillings of existing summer quilts are stuffy, airtight and not easy to release moisture quickly after hygroscopicity, which leads to uncomfortable use and may cause bacterial growth and plaque problems.

Method used

Filling materials are made of uniformly blended with fine denier polyester fiber, acetate fiber, porous hollow polyester fiber and low melting point fiber. Fine denier polyester fiber accounts for 15-30%, acetate fiber accounts for 30-75%, porous hollow polyester fiber accounts for 0-20%, and low melting point fiber accounts for 10-20%.

Benefits of technology

It achieves high breathability, quick dryness and comfortable feel, solving the problem of traditional summer stuffy and impermeable, making the quilt highly breathable, moisture-permeable and dry, and improving sleep and quality of life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an air-permeable and moisture-permeable filling material which is formed by uniformly mixing and carding fine denier polyester fibers, acetate fibers, porous hollow polyester fibers and low-melting-point fibers, the mass ratio of the fine denier polyester fibers is 15-30%, the mass ratio of the acetate fibers is 30-75%, the mass ratio of the porous hollow polyester fibers is 0-20%, and the mass ratio of the low-melting-point fibers is 0-20%. And the mass ratio of the low-melting-point fibers is 10-20%. The filler has the characteristics of high moisture absorption, high air permeability, fluffiness, light weight and soft hand feeling, and is used for filling and manufacturing a quilt, the quilt has the advantages of a traditional chemical fiber quilt, the problem that the traditional chemical fiber quilt is stuffy and does not dissipate heat is solved, the quilt is highly air-permeable, moisture-permeable and dry, people feel comfortable when the quilt is covered on the body, and the service life of the quilt is prolonged. Therefore, the sleep and life quality can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quilts, and more particularly to a filling material with high air permeability, moisture permeability and quick drying. Background Art

[0002] Quilts are essential items in people's lives. In order to ensure that users can get a comfortable and healthy sleep, as people's quality of life improves, people's requirements for quilts are getting higher and higher, especially for the air permeability and moisture permeability of summer quilts used in summer.

[0003] At present, the filling material of summer quilts is mainly polyester fiber. However, the moisture regain of polyester fiber is low, which leads to the problem that most summer quilts filled with pure chemical fiber are hot and airtight. Pure cotton filling has good moisture absorption, but the fiber has poor moisture release, which means that they are not easy to release moisture quickly after absorbing moisture. Due to long-term use, this may cause bacteria to breed. In addition, summer quilts filled with pure cotton are not easy to dry after washing, and are also prone to hardening. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a breathable and moisture-permeable filling material to solve the defects of the prior art.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] A breathable and moisture-permeable filling material, characterized in that it is made of fine-denier polyester fibers, acetate fibers, porous hollow polyester fibers and low-melting-point fibers uniformly mixed and combed, wherein:

[0007] The mass proportion of the fine-denier polyester fiber is 15-30%, the mass proportion of the acetate fiber is 30-75%, the mass proportion of the porous hollow polyester fiber is 0-20%, and the mass proportion of the low-melting-point fiber is 10-20%.

[0008] In the invention, fine-denier polyester fibers are used to make the filling material as a whole relatively soft, good in touch, and skin-friendly; acetate fibers are used, which have the characteristics of light specific gravity and small initial elastic modulus, excellent softness and lightness, and acetate fibers have a certain number of hydrophilic hydroxyl groups, and the fiber water retention rate can reach a state that the human body feels comfortable, and it will not absorb a large amount of water and swell violently, and has good moisture absorption and release properties, and reflects dimensional stability and quick-drying properties; the use of porous hollow fibers is conducive to air circulation, can take away excess heat, and solve the problem of stuffiness; the use of low-melting-point fibers makes the various fibers in the filling material adhere to each other.

[0009] In a specific embodiment of the present invention, the fine denier polyester fiber has a diameter of 1.0-3D and a length of 45-64 mm.

[0010] In a specific embodiment of the present invention, the acetate fiber has a diameter of 1.2-3.33D and a length of 25-64 mm.

[0011] In a specific embodiment of the present invention, the porous hollow polyester fiber is preferably a four-hole polyester fiber.

[0012] In a specific embodiment of the present invention, the surface of the porous hollow polyester fiber has grooves. The surface of the porous hollow polyester fiber has grooves, which makes it easier to discharge moisture and has better moisture removal and heat dissipation effects.

[0013] In a specific embodiment of the present invention, the diameter of the four-hole polyester fiber is 5D-7D and the length is 55-70 mm. Such four-hole polyester fibers of such thickness have a certain supporting force, making the filling relatively fluffy.

[0014] In a specific embodiment of the present invention, the low-melting point fiber is one of low-melting point polyolefin fiber, low-melting point copolyester fiber, low-melting point copolyamide fiber, low-melting point corn fiber, or a composite fiber thereof.

[0015] It can be seen from the above detailed description that the filling material of the present invention has the characteristics of high moisture absorption, high air permeability, fluffiness, light weight and soft hand feel. When used as a filling material to make a quilt, the quilt has the advantages of a traditional chemical fiber quilt while solving the problem of the traditional chemical fiber quilt being stuffy and not being able to dissipate heat, making the quilt highly breathable, moisture permeable and dry, making people feel comfortable when covering themselves, thereby improving the quality of sleep and life. DETAILED DESCRIPTION

[0016] The technical solution in the present invention is described clearly and completely below. In addition, the forms of the various structures described in the following embodiments are merely illustrative, and the present invention is not limited to the various structures described in the following embodiments. All other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0017] The air-permeable and moisture-permeable filler of the present invention is formed by uniformly mixing and combing fine-denier polyester fibers, acetate fibers, porous hollow polyester fibers and low-melting-point fibers, wherein: the mass proportion of the fine-denier polyester fibers is 15-30%, the mass proportion of the acetate fibers is 30-75%, the mass proportion of the porous hollow polyester fibers is 0-20%, and the mass proportion of the low-melting-point fibers is 10-20%.

[0018] The low melting point fiber is one of low melting point polyolefin fiber, low melting point copolyester fiber, low melting point copolyamide fiber, low melting point corn fiber or a composite fiber thereof.

[0019] In the present invention, the fine denier polyester fiber has a diameter of 1.0-3D and a length of 45-64mm; the acetate fiber has a diameter of 1.2-3.33D and a length of 25-64mm; the porous hollow polyester fiber is preferably a four-hole polyester fiber with grooves on the surface. The diameter of the four-hole polyester fiber is 5D-7D and the length is 55-70mm.

[0020] Example 1

[0021] In this embodiment, the mass proportion of fine-denier polyester fiber is 30%, the mass proportion of acetate fiber is 30%, the mass proportion of porous hollow polyester fiber is 20%, and the mass proportion of low-melting-point fiber is 20%. Among them, the fine-denier polyester fiber is a mixture of 1.2D diameter and 3D diameter, each accounting for 50%, and the length is 64mm; the diameter of acetate fiber is 1.2D and the length is 38mm; the diameter of four-hole polyester fiber is 6.5D and the length is 64mm; the low-melting-point fiber is a low-melting-point polyolefin fiber, with a diameter of 2D and a length of 64mm.

[0022] Example 2

[0023] In this embodiment, the mass proportion of fine-denier polyester fiber is 20%, the mass proportion of acetate fiber is 45%, the mass proportion of porous hollow polyester fiber is 20%, and the mass proportion of low-melting-point fiber is 15%. Among them, the fine-denier polyester fiber is a mixture of 1.2D diameter and 3D diameter, each accounting for 50%, and the length is 64mm; the diameter of acetate fiber is 1.2D and the length is 38mm; the diameter of four-hole polyester fiber is 6.5D and the length is 64mm; the low-melting-point fiber is a low-melting-point polyolefin fiber, with a diameter of 2D and a length of 64mm.

[0024] Example 3

[0025] In this embodiment, the mass proportion of fine-denier polyester fiber is 20%, the mass proportion of acetate fiber is 60%, the mass proportion of porous hollow polyester fiber is 10%, and the mass proportion of low-melting-point fiber is 10%. Among them, the fine-denier polyester fiber is a mixture of 1.2D diameter and 3D diameter, each accounting for 50% by mass, and the length is 64mm; the diameter of acetate fiber is 1.2D and the length is 38mm; the diameter of four-hole polyester fiber is 6.5D and the length is 64mm; the low-melting-point fiber is a low-melting-point polyolefin fiber, with a diameter of 2D and a length of 64mm.

[0026] Example 4

[0027] In this embodiment, the mass proportion of fine-denier polyester fiber is 15%, the mass proportion of acetate fiber is 75%, and the mass proportion of the low-melting-point fiber is 10%. Among them, the fine-denier polyester fiber is a mixture of 1.2D diameter and 3D diameter, each accounting for 50% by mass, and the length is 64mm; the diameter of acetate fiber is 1.2D and the length is 38mm; the diameter of four-hole polyester fiber is 6.5D and the length is 64mm; the low-melting-point fiber is a low-melting-point polyolefin fiber, with a diameter of 2D and a length of 64mm.

[0028] Comparative Example

[0029] The comparative example is a mixture of 85% by mass of fine-denier polyester fiber and 15% by mass of low-melting-point fiber. The fine-denier polyester fiber is a mixture of 50% diameter 1.2D and 50% diameter 3D, and the length is 64mm. The low-melting-point fiber is a low-melting-point polyolefin fiber, with a diameter of 2D and a length of 64mm.

[0030]

Production method

[0031] The air-permeable and moisture-permeable filling of the present invention is prepared by mixing and removing impurities, opening, combing, drying, ironing, and slicing the above four fibers according to the mass ratio of Example 1, Example 2, Example 3, Example 4, and the comparative example. The specific steps are as follows:

[0032] Mixing and impurity removal step. Use an automatic reciprocating cotton mixer to mix and remove impurities from various fibers. The feeding frequency of the cotton mixer is 30Hz, the mixing time is 80s, and the walking speed is 17m / min. This step is to loosen the raw materials and remove various impurities.

[0033] Opening step. The preliminarily treated mixed fiber is sent to the single-axis flow opener through the cotton pipe and the fan. The beater of the opener is 3000W; the speed is 960r / min, and the cotton feeding roller is 0.55KW. The mixed fiber is evenly and densely beaten multiple times in a free state to form a fiber flow. This step can tear the large fiber clumps and blocks into small pieces and small bundles for uniform mixing so that the fluffy feel can be combed out later.

[0034] Combing step. The fiber flow passes through the bucket box and enters the carding machine for carding. The power of the carding machine is 6000W, the maximum speed of the carding machine belt scale is 28m / min, the belt scale width is 0.420m, the cotton feeding speed is 8.75m / min, the reciprocating curtain base speed is 26m / min, and the main cylinder speed is 34.9Hz.

[0035] Drying step. The carding machine sends the combed mixed fibers into the dryer for drying. The temperature of the drying area is 180°C, the fan frequency is 20Hz; the walking frequency is 16Hz, and the cooling fan frequency is 40Hz. In this step, the low-melting point fibers are heated so that they are uniformly and effectively melt-bonded with other fibers at the intersection, so that various fibers are bonded to each other.

[0036] Ironing step. The dried fibers are ironed with an ironing machine power of 3000W, a temperature of 250℃, and a speed of 8m / min. Ironing melts the fibers on the surface, making both sides smooth and reducing the risk of fibers coming out of the fabric after washing.

[0037] Slicing step: Slicing is performed after the ironing step to obtain the filling material of each embodiment of the present invention.

[0038]

test

[0039] The fillers of Example 1, Example 2, Example 3 and Example 4 prepared above all have a very soft feel when touched.

[0040] The samples prepared in Example 1, Example 2, Example 3, Example 4 and the comparative example were also subjected to a fluffiness test, an air permeability test, a moisture absorption performance test and a moisture release performance test.

[0041] <Bulkyness Test>

[0042] Test method:

[0043] The samples were made into flakes with a mass density of 100 gsm and a size of 50 cm × 50 cm. Each flake was folded in four and the height after folding was measured. The measurement results are shown in Table 1.

[0044] Table 1 Bulkiness test results (unit: cm)

[0045] Example 1 Example 2 Example 3 Example 4 Comparative Example 9 8.8 8.6 8.2 6.5

[0046] It can be seen from the above table that the folding height of the flakes produced in Examples 1 to 4 is significantly higher than that of the comparative example, indicating that the filling material of the present invention has good fluffiness.

[0047] <Air permeability test>

[0048] Test method: Tested in accordance with the national standard "Textiles_Determination of fabric air permeability" (GB5453-1997). The test results are shown in Table 2.

[0049] Table 2 Air permeability test results (unit: mm / s)

[0050] Example 1 Example 2 Example 3 Example 4 Comparative Example 2232 2892 2579 2366 1073

[0051] As can be seen from the above table, the air permeability of Examples 1 to 4 is significantly better than that of the comparative example, indicating that the filling material of the present invention has excellent air permeability.

[0052] <Moisture absorption performance test>

[0053] Test method:

[0054] After the sample is dried in an oven (temperature 105°C) (dry to constant weight), it is weighed immediately after cooling and the weight M0 (in g) is recorded. Then it is placed in a constant temperature and humidity environment (standard atmospheric temperature 20±3°C, humidity 65±4%) to absorb moisture, and the weight is weighed at regular intervals and recorded as M0. t (Unit: g). Calculate the weight difference M after moisture absorption over time. The calculation formula is: M = M t -M0; Calculate the mass difference rate over time, the calculation formula: ΔM=(M t -M t-1) / M t × 100%. The test results are shown in Table 3.

[0055] Table 3 Hygroscopicity test results

[0056]

[0057] As can be seen from the above table, the moisture absorption effect of Examples 1 to 4 is significantly better than that of the comparative example for the same 30-minute moisture absorption effect, especially Example 4, which has the highest moisture absorption difference rate of 2.238% in 30 minutes, reflecting the advantage of fast moisture absorption of Examples 1 to 4. In addition, it can also be seen from the above table that the moisture absorption duration of Examples 1 to 4 is also longer than that of the comparative example, especially Example 4, which has a moisture absorption duration of 150 minutes. These fully illustrate that Examples 1 to 4 have fast moisture absorption, long moisture absorption duration, and significantly better moisture absorption effect than the comparative example, and also reflect that the higher the acetate content, the better the moisture absorption effect.

[0058] <Dehumidification performance test>

[0059] Test method:

[0060] After the sample is placed in a constant temperature and humidity oven (temperature 20℃±3℃, humidity 90±4%) for 15 hours, it is weighed and recorded as m0 (in g). Then it is placed in a constant temperature and humidity environment (temperature 20±3℃, humidity 65±4%) to release moisture, and the sample is weighed every 30 minutes and recorded as m0 (in g). t (in g), calculate the mass difference m (in g) after dehumidification over time: m = m0-m t ; Calculate the difference rate of moisture release mass over time, the calculation formula is: Δm = (m t -mt-1 ) / m t × 100%. The test results are shown in Table 4.

[0061] Table 4 Dehumidification performance test results

[0062]

[0063] As can be seen from the above table, the dehumidification effects of Examples 1 to 4 are significantly better than those of the comparative example for the same 30-minute dehumidification effect, especially Example 4, which has the highest dehumidification difference rate of -0.548% in 30 minutes, reflecting the advantages of Examples 1 to 4 having fast dehumidification. In addition, it can also be seen from the above table that the dehumidification duration of Examples 1 to 4 is also longer than that of the comparative example, especially Example 4, which has a dehumidification duration of 180 minutes. These fully illustrate that Examples 1 to 4 have fast dehumidification, long dehumidification duration, and significantly better dehumidification effects than the comparative example, and also reflect that the higher the acetate content, the better the dehumidification effect.

[0064] Through the above detailed introduction, it can be explained that the filling material of the present invention has the characteristics of high moisture absorption, high air permeability, fluffiness, light weight and soft hand feel. When used as a filling material to make a quilt, the quilt has the advantages of a traditional chemical fiber quilt while solving the problem of the traditional chemical fiber quilt being stuffy and not being able to dissipate heat, making the quilt highly breathable, moisture permeable and dry, making people feel comfortable when covering themselves, thereby improving the quality of sleep and life.

Claims

1. A breathable and moisture-permeable filling material, characterized in that: It is made of fine-denier polyester fiber, acetate fiber, porous hollow polyester fiber and low-melting-point fiber, which are evenly mixed and combed, including: The mass proportion of the fine-denier polyester fiber is 15-30%, the mass proportion of the acetate fiber is 30-75%, the mass proportion of the porous hollow polyester fiber is 0-20%, and the mass proportion of the low-melting-point fiber is 10-20%.

2. The air-permeable and moisture-permeable filling material according to claim 1, characterized in that: The fine denier polyester fiber has a diameter of 1.0-3D and a length of 45-64mm.

3. The air-permeable and moisture-permeable filling material according to claim 1, characterized in that: The acetate fiber has a diameter of 1.2-3.33D and a length of 25-64mm.

4. The air-permeable and moisture-permeable filling material according to claim 1, characterized in that: The porous hollow polyester fiber is a four-hole polyester fiber.

5. The air-permeable and moisture-permeable filling material according to claim 1, characterized in that: The porous hollow polyester fiber has grooves on its surface.

6. The air-permeable and moisture-permeable filling material according to claim 1, characterized in that: The four-hole polyester fiber has a diameter of 5D-7D and a length of 55-70 mm.

7. The air-permeable and moisture-permeable filling material according to claim 1, characterized in that: The low melting point fiber is one of low melting point polyolefin fiber, low melting point copolyester fiber, low melting point copolyamide fiber, low melting point corn fiber or a composite fiber thereof.

Citation Information

Patent Citations

  • Artificial staple fibres fluffing up process

    CA441412A

  • Ultrathin and ultra-thermal core quilt and preparation method thereof

    CN105795803A

  • 15D porous hollow fiber home textile cotton and preparation method thereof

    CN107012519A

  • Polyester fiber filling materials and filling process therefor

    CN1966789A

  • Warm-keeping interior fabric for automobile

    CN216998776U